Hydrodynamic growth and mix experiments at National Ignition Facility. (March 2016) - Smalyuk, V. A.; Caggiano, J.; Casey, D.; Cerjan, C.; Clark, D. S.; Edwards, J.; Grim, G.; Haan, S. W.; Hammel, B. A.; Hamza, A.; Hsing, W.; Hurricane, O.; et al.
Abstract: Hydrodynamic growth and its effects on implosion performance and mix were studied at the National Ignition Facility (NIF). Spherical shells with pre-imposed 2D modulations were used to measure Rayleigh-Taylor (RT) instability growth in the acceleration phase of implosions using in-flight x-ray radiography. In addition, implosion performance and mix have been studied at peak compression using plastic shells filled with tritium gas and imbedding localized CD diagnostic layer in various locations in the ablator. Neutron yield and ion temperature of the DT fusion reactions were used as a measure of shell-gas mix, while neutron yield of the TT fusion reaction was used as a measure of implosion performance. The results have indicated that the low-mode hydrodynamic instabilities due to surface roughness were the primary culprits to yield degradation, with atomic ablator-gas mix playing a secondary role.